Cooperative and immersive coaching to facilitate skill development in construction tasks - Hou, L.; Chi, Hung-Lin; Utiome, E.; Wang, Xiangyu (2016)
At present, construction operations training offered by qualified organisations and associations for the Australian oil and gas, mineral and chemical industries have been provided at only limited levels. Moreover, the relevant training facilities and centres being established or considered in the construction agenda are insufficient to meet the growing standard of operators and industry expansion. These facts illustrate the need for developing effective cooperative coaching and learning systems for expediting the acquisition of fundamental construction skills. Accordingly, the aim of this ongoing study is to establish scientific principles for developing appropriate Virtual Reality (VR) and Augmented Reality (AR) supported cooperative and immersive training prototypes and curriculum to meet the above mentioned purposes. Through the application of pertinent learning theories, system prototyping and experimentation techniques, this study is envisioned to significantly supplement interactive and immersive site experiences from immersive training environment, and produce cost-effective and efficient ways to manage the skill shortage challenges in mega construction projects.